BELAJAR PIANIKA DENGAN METODE TUTOR SEBAYA KELAS X IPA 3 DI SMA NEGERI 7 PADANG - Yusra, Ahmad Fauzan; Sudarman, Yos (SENDRATASIK UNP, 2019)
Abstract This study aims to describe how the implementation of pianika learning by using the peer tutoring method at class X IPA 3 on cultural art subject in SMA N 7 Padang.Type of the research was qualitative with using descriptive analysis method approach. The main instrument of this study was the researcher and it was supported with supporting instruments such as stationery and camera. Techniques of data collection were carried out by doing observation, interview and literature study. The steps in analyzing data were collecting, describing, and making conclusion.The result shows that in the implementation of the peer tutoring method in SMA N 7 Padang obtains satisfactory result for teacher and students. Students who initially have problems in capturing the subject are already able to receive the lesson well and students who become tutors also get new experiences such as they can speak in public and also learn how to share knowledge. During learning, the teacher is a facilitator and motivator who actively guides the students. Based on the result of the pianika practice examination, all of students get grades above the KKM or above 80 and only one that is incomplete because having special needs. Keywords: learn pianics, Peer tutor methods